Enzyme immobilization and its applications in food processing: A review - Nadia Bashir; Monika Sood; Julie D Bandral (2020)
The “immobilized enzymes” are the enzymes physically confined or localized in a certain defined region of space with retention of their catalytic activities which can be used repeatedly and continuously. Enzyme immobilization provides an excellent base for increasing availability of enzyme to the substrate with greater turnover over a considerable period of time. Immobilized enzymes are preferred over their free counterpart due to their prolonged availability that reduces redundant downstream and purification processes. The enzymes can be attached to the support by interactions ranging from reversible physical adsorption and ionic linkages to stable covalent bonds. The choice of the most appropriate immobilization technique depends on the nature of the enzyme and the carrier. Such techniques produce immobilized enzymes of varying stability due to changes in the surface microenvironment and degree of multipoint attachment. The industrial applications of immobilised enzymes are progressively increasing. Immobilized enzymes find use in a number of biotechnological products with applications in diagnostics, bio affinity chromatography, and biosensors. Immobilised enzymes find wide applications in the food industry. With these immobilised enzymes, it is possible to obtain different types of sugar syrups, lactose free milk, clarified and debittered juices and wines. Immobilised enzymes can be employed for the production of different active packaging material like oxygen scavenging, anti-microbial films. However, commercialization of immobilized enzymes is still at a slower pace because of their costs and storage problems. Research should be focused to overcome the current limitations related to immobilization techniques, so as to expand the horizon for all-round application. In future, immobilized enzymes are going to play a vital role in various industries including pharmaceuticals, chemicals, food and fuel.